The impact of climate change-related disasters on mental health and epigenetics: a narrative review - Roe, Emma Antonina; Khov, Engluy; Kim, Hannah; Demelo, Beth; Zavitz, Savannah; Cao-Lei, Lei (Frontiers in Epigenetics and Epigenomics, 2024)
Climate change has contributed to an increase in the frequency and intensity of natural disasters such as droughts, wildfires, hurricanes, and floods, leading to both immediate physical harm and long-term mental health consequences. Survivors often experience psychological distress, including anxiety, depression, and post-traumatic stress disorder (PTSD), as a result of these traumatic events. This narrative review explores the intersection of climate change-related disasters, mental health outcomes, and epigenetic modifications. Specifically, we summarize recent findings on how environmental stressors influence both mental health and epigenetic changes, such as DNA methylation. Emerging evidence suggests that epigenetic mechanisms, particularly DNA methylation, could mediate the effects of climate change-related stress on mental health, potentially contributing to the onset of mental disorders like depression, panic disorder, autism spectrum disorder, and attention deficit hyperactivity disorder. We also discuss other epigenetic mechanisms, such as histone modifications and non-coding RNAs, and emphasize the importance of longitudinal studies to capture the dynamic nature of epigenetic changes over time. Finally, we propose future research directions to deepen our understanding of the complex relationships between climate change-related disasters, mental health outcomes, and epigenetic mechanisms, which will pave the way for more effective mental health interventions and policy integration.